New Neurons in Aging Brains: Molecular Control by Small Non-Coding RNAs - Schouten, Marijn; Buijink, M R.; Lucassen, Paul J.; Fitzsimons, Carlos P. (Frontiers in Neuroscience, 2012)
Adult neurogenesis is a process that continues in the adult and also aging brain. It generates functional neurons from neural stem cells present in specific brain regions. This phenomenon is largely confined to two main regions: the subventricular zone of the lateral ventricle, and the subgranular zone of the dentate gyrus, in the hippocampus. With age, the hippocampus and particularly the dentate gyrus are affected. For instance, adult neurogenesis is decreased with aging, in both the number of proliferating cells as well as their neuronal differentiation, while in parallel an age-associated decline in cognitive performance is often seen. Surprisingly, the synaptogenic potential of adult-born neurons appears unaffected by aging. Therefore, although proliferation, differentiation, survival and synaptogenesis of adult-born new neurons in the dentate gyrus are closely related to each other, they appear differentially regulated with aging. In this review we discuss the crucial role of a novel class of recently discovered regulators of gene expression, i.e. the small non-coding RNAs, in the development of adult neurogenesis from neural stem cells to functionally integrated neurons. In particular, a subgroup of the small non-coding RNAs, the microRNAs, fine-tune many events during adult neurogenesis progression. Moreover, multiple small non-coding RNAs are differentially expressed in the aged hippocampus. This makes small non-coding RNAs appealing candidates to orchestrate, and possibly correct or prevent, the functional alterations in adult neurogenesis and cognition associated with aging. Finally, we briefly summarize observations that link changes in circulating levels of steroid hormones with alterations in adult neurogenesis and subsequent vulnerability to psychopathology in advanced age, and discuss a possible role of microRNAs in stress-associated alterations in adult neurogenesis during aging.